THE EFFECT OF CORPORATE GOVERNANCE AND b OWNERSHIP STRUCTURE ON SUSTAINABILITY REPORTING QUALITY AS A FINANCIAL SIGNAL: (AN EMPIRICAL STUDY OF FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2021–2024 PERIOD) - Muh. Fahri Reza; Cornelia Matani; Klara Wonar; Alfiana Antoh (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study aims to analyze the effect of corporate governance and ownership structure on sustainability reporting quality as a financial signal in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Corporate governance in this study is proxied by the size of the board of commissioners and gender diversity of the board of commissioners, while ownership structure is proxied by managerial ownership and institutional ownership. Sustainability reporting quality is considered a non-financial signal that reflects corporate transparency and commitment to sustainable business practices. This research employs a quantitative approach using panel data regression analysis. The sample was selected through purposive sampling, resulting in 11 companies with a total of 44 observations. The data used in this study are secondary data obtained from annual reports, sustainability reports, and share ownership information published by the companies and the Indonesia Stock Exchange. Data analysis was conducted using EViews software. The results indicate that institutional ownership has a positive and significant effect on sustainability reporting quality. Meanwhile, the size of the board of commissioners, gender diversity of the board of commissioners, and managerial ownership do not have a significant effect on sustainability reporting quality. Simultaneously, corporate governance and ownership structure do not have a significant effect on sustainability reporting quality. These findings suggest that improvements in sustainability reporting quality are not solely influenced by corporate governance mechanisms and ownership structure, but also by other factors outside the research model